ECB vs Bundesbank: Diverging tones and policy effectiveness - Peter Tillmann; Andreas Walter (Philipps-University Marburg, School of Business and Economics, 2018)
The present paper studies the consequences of conflicting narratives for the transmission of monetary policy shocks. We focus on conflict between the presidents of the ECB and the Bundesbank, the main protagonists of monetary policy in the euro area, who often disagreed on policy over the past two decades. This conflict received much attention on financial markets. We use over 900 speeches of both institutions' presidents since 1999 and quantify the tone conveyed in speeches and the divergence of tone among both both presidents. We find (i) a drop towards more negative tone in 2009 for both institutions and (ii) a large divergence of tone after 2009. The ECB communication becomes persistently more optimistic and less uncertain than the Bundesbank's after 2009, and this gap widens after the SMP, OMT and APP announcements. We show that long-term interest rates respond less strongly to a monetary policy shock if ECB-Bundesbank communication is more cacophonous than on average, in which case the ECB loses its ability to drive the slope of the yield curve. The weaker transmission under high divergence reflects a muted adjustment of the expectations component of long-term rates.
Keywords: E52; E43; E32; 330; Central bank communication; diverging tones; speeches; text analysis; monetary transmission